The Symbol of Satanism in The Nun Movie (Roland Barthes Semiotic Analysis) - Rafi Warsa Junia (Experimental Student Experiences, 2024)
The purpose of this study was to find out the symbols of Satanism in the movie 'The Nun'. The method used is a qualitative methodology using Roland Barthes' semiotic analysis. The techniques of data collection in this study are observation, documentation and interviews. The results of this study show that there are several symbols of Satanism contained in the film 'The Nun' through stages of denotation, connotation and myth in Roland Barthes' semiotics, namely, a) the symbol of the inverted cross attached to the wall, b) the magic book shows the contents in the book such as symbols of demons and magic spells, d) the symbol of the five-pointed inverted star (Pentagram ) engraved on Sister Irene's body, e) the serpent symbol shown when Father Burke, Sister Irene and Frenchie entered the church. The conclusion of this study is the existence of several symbols of Satanism such as the Pentagram, Inverted Cross, snake (Serphent). Each symbol has its own meaning for adherents and followers of Satanism.